Rural livelihoods in changing, multifunctional landscapes - Noordwijk, Meine van; Onyango, Leah; Kalinganire, Antoine; Joshi, Laxman; Hoang, Minh Ha; Ndichu, Nestry; Jamnadass, Ramni H. (World Agroforestry Centre, 2011)
The main argument in this section is that changing (or 'transforming') landscapes and lives are mutually dependent on each other, as they are closely linked in time and space. Within the landscape continuum, the roles of landscape elements in supplying goods and services to local livelihoods, however, shift with the stage of development and substitution of traded and imported goods and services for those provided locally and potentially used as sources of income.